A combustion phasing control-oriented model applied to an RCCI engine. Issue 31 (2018) - Guardiola, C.; Pla, B.; Bares, P.; Barbier, A.
Abstract: Low temperature combustions such as Reactivity Controlled Compression Ignition (RCCI) have been shown to be a promising way to reduce pollutants at the exhaust, i.e. NOx and soot emissions, and increase the thermal efficiency of future engines. However, such concepts are subject to substantial control sensitivity, e.g. combustion phasing, due to their lack of direct actuation for controlling the ignition of the mixture. This work investigates a control-oriented model based on physical equations aimed to predict the start of combustion and the crank angle of 50% fuel burnt (CA50). The model was developed for predicting the ignition using a modified knock integral model and a linear equation was used to estimate the burn duration between the start of combustion and the combustion phasing. The calibration and the validation of the model were performed using experimental data from a heavy-duty engine showing good results under transient operation.